2021
DOI: 10.1186/s12880-021-00623-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic 18F-FDG PET imaging of liver lesions: evaluation of a two-tissue compartment model with dual blood input function

Abstract: Background Dynamic PET with kinetic modeling was reported to be potentially helpful in the assessment of hepatic malignancy. In this study, a kinetic modeling analysis was performed on hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC) from dynamic FDG positron emission tomography/computer tomography (PET/CT) scans. Methods A reversible two-tissue compartment model with dual blood input function, which takes into consideration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(41 citation statements)
references
References 30 publications
1
40
0
Order By: Relevance
“…The blood supply of background liver tissue differs from that of HCCs;background liver tissue is mainly supplied by the portal vein, which accounts for 70%−80% of the total inflow blood flow. 3,12,44 The parameter fa (0.758 ± 0.202 vs. 0.316 ± 0.207) obtained by the proposed Bayesian method is closer to the clinical physiological value than the fa value obtained by the NLLS method (0.724 ± 0.317 vs. 0.205 ± 0.231). The results of the present experiment are consistent with those of previous studies, 3,6 showing a significantly higher fa in HCCs than in background liver tissues.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The blood supply of background liver tissue differs from that of HCCs;background liver tissue is mainly supplied by the portal vein, which accounts for 70%−80% of the total inflow blood flow. 3,12,44 The parameter fa (0.758 ± 0.202 vs. 0.316 ± 0.207) obtained by the proposed Bayesian method is closer to the clinical physiological value than the fa value obtained by the NLLS method (0.724 ± 0.317 vs. 0.205 ± 0.231). The results of the present experiment are consistent with those of previous studies, 3,6 showing a significantly higher fa in HCCs than in background liver tissues.…”
Section: Discussionmentioning
confidence: 82%
“…Since the liver receives blood from both the hepatic artery and the portal vein, the dual-input threecompartment model provides more accurate kinetic modeling parameters than other models. 3,14 The nonlinear least squares (NLLS) method is the most common method for estimating kinetic parameters 3,6,8,9 ; however, this approach is not suitable for estimating kinetic parameters from clinical data with low signal-to-noise ratios 15 and is prone to falling into local minima. 12,16,17 Deep learning enables output parametric images without requiring the input function, 18,19 but it can only generated image of a single parameter and the construction of the model requires datasets from a large number of samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positron emission tomography (PET)-CT imaging of liver function using flourine (F) tagged fluoro-D-galactose (FDGal, a galactose analog metabolised by hepatic cells) has also been used to quantify hepatic metabolic function [ 27 , 28 ]. Tracer kinetic modeling of the dynamic signal has been used to also derive quantitative tissue perfusion parameters such as hepatic arterial or portal venous blood flow and volume [ 29 ]. A clinical trial is underway at the Princess Alexandria Hospital in Australia to evaluate the use of F-FDGal PET for liver function assessment and to predict toxicity of liver SBRT ( , accessed on 27 September 2022).…”
Section: Liver Function Assessmentmentioning
confidence: 99%
“…Sarkar et al [ 8 ] demonstrated that dynamic 18 F-FDG PET with tracer kinetic modeling has the potential to diagnose nonalcoholic steatohepatitis. Wang et al [ 9 ] found that dynamic 18 F-FDG PET with optimization-derived blood input function kinetic modeling can effectively distinguish liver lesions. Considering 60-min or more dynamic PET/CT is not easily available in routine clinical settings.…”
Section: Introductionmentioning
confidence: 99%